Gereja Ekstra Biblikal dan Tanggung Jawab dalam Menyelesaikan Amanat Agung - Y. M. Imanuel Sukardi (KHARISMATA: Jurnal Teologi Pantekosta, 2019)
There has emerged a kind of phenomenon of extra-biblical churches in present days. This article is a qualitative study that aimed to explain the phenomenon of the extra-biblical church. By using the descriptive analysis method on the extra-biblical church phenomenon, there are some findings concluded from this study, namely: First, the extra-biblical church is a church whose existence and legitimacy exceeds Bible standards, its pattern and behavior exceed the demands of the Bible. Secondly, the extra-biblical church legitimized by tradition, traditional and traditional forms have several deadly good traditions such as the tradition of growth not multiplication, the tradition of teaching not obedience, the tradition of service in not outreach and so on; Third, the extra-biblical church is oriented and has a mega church structure that is so complex and very expensive that it is difficult to duplicate and multiply. As a result, there is a decrease in intensity in carrying out the grand mandate. AbstrakBelakangan ini muncul semacam fenomena gereja ekstra biblikal. Ini merupakan kajian kualitatif yang bertujuan untuk menjelaskan fenomena gereja ekstra biblikal tersebut. Dengan menggunakan metode analisis deskriptif pada fenomena gereja ekstra biblikal tersebut, ada beberapa kesimpulan yang didapat dari kajian ini, yakni: Pertama, gereja ekstra biblikal adalah gereja yang eksistensi dan legitimasinya melebihi standar Alkitab, pola dan perilakunya melampaui tuntutan Alkitab. Kedua, gereja ekstra biblika dilegitimasi oleh tradisi, berpaham dan berbentuk tradisional memiliki beberapa tradisi baik yang mematikan seperti tradisi pertumbuhan bukan pelipatgandaan, tradisi pengajaran bukan ketaatan, tradisi pelayanan ke dalam bukan penjangkauan ke luar dan sebagainaya; Ketiga, gereja ekstra biblika berorentasi dan berstruktur gereja mega yag begitu rumit dan sangat mahal sehingga sulit diduplikasi dan dimultiplikasi. Akibatnya, terjadi penurunan intensitas dalam melakukan amanat agung.